2006
DOI: 10.1002/nur.20156
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue representations in women with heart failure

Abstract: Self-care management of symptoms for persons with heart failure (HF) may only be successful when their representations regarding their symptoms are accurate and linked to appropriate behavioral strategies. The purpose of this secondary data analysis (N = 169 women with HF) was to describe representations of one HF-related symptom, fatigue, and examine whether representations were related to physical health status, health care utilization, and psychological well-being and whether they differed by age. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…10,14,22,31,69-72 The underlying mechanism involves the alleviation of symptoms that are barriers or constraints to physical activity and function, resulting in higher levels of physical activity and function among postoperative CABS patients. Although several studies examined gender differences in CABS outcomes, 4,30,63 little evidence is available regarding gender differences in response to post-CABS interventions and the potential explanatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14,22,31,69-72 The underlying mechanism involves the alleviation of symptoms that are barriers or constraints to physical activity and function, resulting in higher levels of physical activity and function among postoperative CABS patients. Although several studies examined gender differences in CABS outcomes, 4,30,63 little evidence is available regarding gender differences in response to post-CABS interventions and the potential explanatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…26,30 Furthermore, females with depression demonstrated significantly poorer physical functioning. 31,32 …”
Section: Related Literaturementioning
confidence: 99%
“…The role of age in this matter should not be disregarded. Plach et al [8] found that middle-aged women with HF reported more emotional distress and more severe consequences from fatigue than older women.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients do no recognize exaggerating symptoms to worsening of CHF . However, higher levels of distress because of fatigue were associated with higher levels of health care utilization (Plach et al, 2006).…”
Section: Fatigue In Patients With Chronic Heart Failurementioning
confidence: 93%
“…Younger women seemed to be more distressed from fatigue and reported more intrusive consequences in their daily life than older women. (Plach et al, 2006). Older persons seem to accept fatigue and perceive it as less bothersome because they accept it as an inevitable effect of the aging process (Schaefer, 1990;Friedman, 1997).…”
Section: Fatigue In Patients With Chronic Heart Failurementioning
confidence: 99%